Internet addiction and psychological health of students - L. G. Zhdanova; O. V. Zabrodina; A. A. Shakurova (Вестник университета)
The article is devoted to the study of the problem of influence of internet addiction on the psychological health of students. This article discusses such concepts as psychological health and internet addiction as well as analyses the research of various authors on this issue. Thus, after analysing modern research, we have determined that too frequent use of the internet and, subsequently, internet addiction negatively affect the psychological health of an individual. The psychological health is an important aspect of human life in society. In psychological and pedagogical science, there are certain criteria for determining its level. The criteria include genetic characteristics, conditions for successful development, ability to adapt quickly in society, and personality stability. In the educational environment, the psychological health is considered from the positions of priority, personal value of health and value attitude to it, confidence, creativity, adequate perception of the world, intellectual potential, adequate self-esteem and self-perception, interest in other people, stress tolerance, orientation to self-development. To maintain and strengthen the psychological health of the students, in higher education institutions conditions are created, and specially designed programmes, models and socio-psychological training are used.